WORLD ENGLISHES: : REFLECTION ON TEXT COMPLEXITY PROSPECTIVE STUDIES - A. Yarullina, Olesya; H. Tarasova, Fanuza; V. Varlamova, Elena; S. Safonkina, Olga; V. Sazhyna, Elena (Gênero & Direito, 2019)
The following study aims at highlighting new directions of text complexity studies, giving way to more advanced and varied research in the area. It has become the tradition in Russian linguistics as well as foreign one to assess predominantly the complexity of educational texts, thus allowing the learners to boost text comprehension and better material recognition [1], [2], [3], [4]. Text complexity studies can be directed at other types of texts (fiction or newspaper articles) in order to raise the level of awareness and desire to read in general. Bearing in mind that newspaper articles in English can be written by native and non-native speakers, and both types of newspapers can be used in educational purposes, there is urgent need, as we perceive it, to distinguish the features of authentic and Russian English newspaper texts. The research question of upcoming studies can be accomplished as follows: Are English-language newspapers written by Russian speakers of English as ELF comparable with the texts of authentic publications? The results of this study will be interesting in terms of studying the Russian version of the English language as one of the World Englishes in order to demonstrate whether the differences between the English variants are significant. For this purpose, two tools of computational linguistic analysis can be applied: Coh-Metrix, a computational tool that produces indices of the linguistic and discourse representations (developed by Arthur C. Graesser and Danielle McNamara), and L2 Syntactical Complexity Analyzer (L2SCA) developed by Xiaofei Lu at Pennsylvania State University (a computational tool which produces syntactic complexity indices of written English language texts).